(untitled) (Global Journal of Science Frontier Research, 2012)
This study is on the impact of co-operative societies on capital formation using a case study of Temidere-co-operative and Thrift-society, Ijebu-ode, Ogun state. The objectives are to: identify the socio-economic characteristics of the cooperators in the study area; identify the uses of funds of co-operative societies; determine to what extent co-operatives have benefited members in financing their investments; identify problems militating against the effectiveness of co-operative societies; and offer suggestions and recommendations on how to improve the cooperative societies towards enhancing the capital formation of members. The study adopted a non parametric method of analysis which involved Chi-Square method, descriptive statistics and correlation analysis to achieve the stated objectives.